2023
DOI: 10.3390/biomedicines11020596
|View full text |Cite
|
Sign up to set email alerts
|

Comparison among Neuroblastoma Stages Suggests the Involvement of Mitochondria in Tumor Progression

Abstract: Neuroblastoma (NB) is the most common extracranial tumor of early childhood and accounts for 15% of all pediatric cancer mortalities. However, the precise pathways and genes underlying its progression are unknown. Therefore, we performed a differential gene expression analysis of neuroblastoma stage 1 and stage 4 + 4S to discover biological processes associated with NB progression. From this preliminary analysis, we found that NB samples (stage 4 + 4S) are characterized by altered expression of some proteins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…. On the contrary, symptoms of NB vary with site of presentation and include fever, emesis, fatigue, and abdominal masses that often manifest with constipation and abdominal distention that may be painful (23). Fever is a common symptom and is present in 26.0% of pediatric patients with NB, and NB is commonly diagnosed as cancer in infancy, with the median age at diagnosis being approximately 19 months (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…. On the contrary, symptoms of NB vary with site of presentation and include fever, emesis, fatigue, and abdominal masses that often manifest with constipation and abdominal distention that may be painful (23). Fever is a common symptom and is present in 26.0% of pediatric patients with NB, and NB is commonly diagnosed as cancer in infancy, with the median age at diagnosis being approximately 19 months (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…The coordinated stability of MAMs’ structure and function is the material basis for maintaining normal cell physiological function ( 6 , 7 ). Recent studies have shown that abnormal MAMs’ structure and function are closely related to the occurrence and development of many clinical diseases, such as metabolic syndrome ( 8 ), cancer ( 9 ), and neurodegenerative diseases ( 10 ).…”
Section: Introductionmentioning
confidence: 99%